Effect of mycophenolic acid on Epstein-Barr virus infection of human B lymphocytes. - Alfieri, C (1994)
The effect of mycophenolic acid (MPA) on the growth of Epstein-Barr virus (EBV)-transformed B cells and on EBV lytic-cycle gene expression was investigated. MPA inhibited the proliferation of newly infected or established EBV-transformed B-cell lines but was not able to block cell growth transformation or the viral lytic cycle. These results suggest that MPA might reduce transformed-cell proliferation in transplant patients and possibly decrease the risk of development of EBV-related lymphoproliferative disorders.